2015
DOI: 10.1016/j.jamda.2015.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Performance: A Cross-Sectional Study on Serum Vitamin D and Its Interplay With Glucose Homeostasis in Dutch Older Adults

Abstract: This version is distributed under a non-commencial no derivatives Creative Commons (CC-BY-NC-ND) user license, which permits use, distribution, and reproduction in any medium, provided the original work is properly cited and not used for commercial purposes. Further, the restriction applies that if you remix, transform, or build upon the material, you may not distribute the modified material. (25(OH)D) and cognitive performance was examined. Secondly, we assessed 6 whether there was evidence for an interplay b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
1
24
1
Order By: Relevance
“…5,7,8,16,27,[36][37][38][39][40][41] Eight studies reported vitamin D as a continuous variable, 5,6,10,27,29,36,39,42 27 as a categorical variable, and three reported both. Seventeen studies used a-priori cut offs 6,8,[14][15][16]28,34,35,37,41,[43][44][45][46][47][48][49] and 13 categorized into tertiles, 9,17,38,50,51 quartiles, 7,12,18,33 or quintiles. 13,40,52,53 The majority of studies analyzed serum 25OHD with four analyzing plasma 25OHD.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…5,7,8,16,27,[36][37][38][39][40][41] Eight studies reported vitamin D as a continuous variable, 5,6,10,27,29,36,39,42 27 as a categorical variable, and three reported both. Seventeen studies used a-priori cut offs 6,8,[14][15][16]28,34,35,37,41,[43][44][45][46][47][48][49] and 13 categorized into tertiles, 9,17,38,50,51 quartiles, 7,12,18,33 or quintiles. 13,40,52,53 The majority of studies analyzed serum 25OHD with four analyzing plasma 25OHD.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Ten studies classified cognition dichotomously (e.g. decline vs no decline) 9,11,12,17,18,33,43,45,51,53 and 28 reported cognition as a continuous score. Overall, 52 neuropsychological tests were used (Table 1).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations